Survival benefit of neoadjuvant chemotherapy and surgery versus surgery first for resectable colorectal liver metastases: a cohort study. Issue 6 (5th February 2021) - Behrenbruch, Corina; Prabhakaran, Sowmya; Udayasiri, Dilshan; Hollande, Frédéric; Michael, Michael; Hayes, Ian; Heriot, Alexander; Knowles, Brett; Thomson, Benjamin
Abstract : There is continued debate about the survival benefit of neoadjuvant chemotherapy in patients with resectable colorectal liver metastases (CRLM). In this retrospective cohort study, we compared the overall survival and progression‐free survival between patients who received neoadjuvant chemotherapy prior to CRLM resection with those who underwent CRLM upfront. A multivariable Cox proportional hazard regression analysis was performed to adjust for potential confounders. Abstract: Background: There is continued debate about the survival benefit of neoadjuvant chemotherapy (neoCT) in patients with resectable colorectal liver metastases (CRLM). Methods: In this retrospective cohort study, we included 201 patients with metastatic colorectal cancer who underwent their first CRLM resection and achieved resection of all sites of disease. We compared the overall survival (OS) and progression‐free survival (PFS) between patients who received neoCT prior to CRLM resection with those who underwent CRLM upfront. A multivariable Cox proportional hazard regression analysis was performed to adjust for potential confounders. Results: A total of 101 of 201 (51.2%) patients received chemotherapy prior to CRLM resection and 100 of 201 had surgery upfront. Multivariable Cox proportional hazard regression showed no statistically significant difference in the hazard of death for those given neoCT prior to resection of CRLM compared with surgery first for both OS and PFS (OS: hazard ratio 1.74, 95% confidence interval 0.85–3.55, P = 0.127, PFS: hazard ratio 1.42, 95% confidence interval 0.93–2.19, P = 0.107). Conclusion: In our series of patients with metastatic colorectal cancer who achieved surgical resection of all sites of disease, neoCT prior to CRLM resection was not associated with any survival benefit.